El tratamiento jurídico de las migraciones internacionales a través de las regulaciones globalistas de gestión de mano de obra - Barbero González, Iker (Oñati Socio-Legal Series, 2011)
This article deals with the emerging global tendency to regulate international migrations, not by regarding a universal humanitarian and labour Law, but according to neoliberal normative production standards: flexibility, informality, governance… Supranational institutions such as the WTO, the IOM or the EU are establishing normative agreements (GATS, the NAFTA, the EEC…) that regulate migrations as labour and in profit of the global markets. The new contractual models become fragmented titles that recognize rights as immigrant workers and not as a persons or human beings, placing in a legal limbo those who migrate outside the established mechanisms and that not meet the qualification requirements of the global workforce. This text is addressed to the analysis of the categorization of migrants as disposable labour in the global management of the flows.